2021
DOI: 10.1016/j.isci.2021.103231
|View full text |Cite
|
Sign up to set email alerts
|

Inequitable and heterogeneous impacts on electricity consumption from COVID-19 mitigation measures

Abstract: The COVID-19 pandemic has exacerbated energy insecurity and economic hardship among vulnerable populations. This paper provides robust empirical evidence of the degree to which COVID-19 mitigation measures, especially the mandates of school closure and limiting business operations, have impacted electricity consumption behavior in low-income and ethnic minority groups in the United States. We use a regression discontinuity design applied to individual-consumer-level high-frequency smart meter data in Arizona a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The impact of the lockdown on SMEs in developing economies have been seriously underestimated. Lou et al (2021) found that the mandates of school closures and limiting business operations significantly reduced the electricity consumption of SMEs in retail sector by 8% compared to 4% in large businesses in the United States. By contrast, we observed a 70% reduction in retail sector of electricity consumption of SMEs in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of the lockdown on SMEs in developing economies have been seriously underestimated. Lou et al (2021) found that the mandates of school closures and limiting business operations significantly reduced the electricity consumption of SMEs in retail sector by 8% compared to 4% in large businesses in the United States. By contrast, we observed a 70% reduction in retail sector of electricity consumption of SMEs in China.…”
Section: Discussionmentioning
confidence: 99%
“… Blázquez et al (2013) indicated that weather conditions have a significant impact on electricity use. Lou et al (2021) insisted that in addition to temperature, the day of the week is a significant driver of electricity consumption. Therefore, we chose daily temperature, weekend dummy variables and the number of new confirmed cases as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…The preventative public health measures imposed to curtail the pandemic not only led to economic disruption but also changed energy consumption patterns. A study of smart meter data in Arizona and Illinois, for example, found that residential energy use increased while commercial energy use declined, reflecting that people spent more time at home during this period, whereas businesses were required to curtail hours or shutdown altogether [22]. Moreover, these consumption changes were starker for populations already more likely to experience higher energy burdens [23] and carry utility debt [24,25], particularly people of color and low-income households [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…Over this time and during the onset of the pandemic, households of color, those with young children, and those that rely on at-home electronic medical devices were significantly more likely to face utility disconnections ( 8 ). These disparities were exacerbated by the pandemic and the resulting economic recession, which left millions out of work ( 9 ) and increased rates of residential energy consumption and costs ( 10 ).…”
mentioning
confidence: 99%